PENGEMBANGAN MEDIA MATH POWER GAMES BERKONSEP GAMIFIKASI UNTUK PENGUATAN LITERASI NUMERASI SISWA - Nur'Aida, Martalia; Permana, Erwin Putera; Imron, Ilmawati Fahmi (Jurnal Pendidikan Dasar, 2024)
This research develops a learning media math power games with an innovative and fun. Innovative and fun to help students complete easily in strengthening numeracy literacy. This research aims to improve the numeracy literacy skills of grade 5 students at SDN Gedangsewu 1. This research method uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were 49 students. The test results of media experts and material experts reached 87% with a very valid category. Practicality was calculated and obtained a score of 90%. The KBK score was 97.14 and the average posttest score was 96.28 with a very effective category. These achievements show that Math Power Games media is suitable for use in learning to improve numeracy literacy of grade V students and also encourage teachers to develop innovative learning tools.